Risk factors associated with the histological grade of canine mast cell tumor based on Kiupel’s two-tier classification of malignancy - Cano-Botero, Andy; Zapata-Cardona, Juliana (Revista Colombiana de Ciencias Pecuarias, 2025)
Background: mast cell tumor (MCT) is one of the most common neoplasms in canines, and histological grading is crucial for its prognosis. However, there is limited local information on the influence of factors such as sex, age, breed, and anatomical location of the lesion on the malignancy grade of this neoplasm. These factors are important for risk assessment and understanding the biological behavior of the tumor. Objective: to assess the association between risk factors (sex, age, breed, anatomical location) and histological grade of MCTs diagnosed at the Animal Pathology Laboratory of the Universidad de Antioquia between 2019 and 2023. Methods: retrospective study based on histopathology reports of canine biopsies; filtering patients diagnosed with MCT. Data on year of report, dog, and tumor characteristics were extracted. Descriptive statistics were presented as relative frequencies, 95% confidence intervals (CI), and Z-tests and Chi-square tests were used to identify differences between proportions. Results: 409 cases of canine MCT were analyzed, of which 74.8% were low grade (LG) and 25.2% high grade (HG). Females presented a higher frequency of high grade MCT (HG-MCT) (50.5%), with no significant differences by sex (p>0.05). Patients aged 5 to 8 years showed greater predisposition to low grade MCT (LG-MCT), while those aged 9 to 16 years to HG-MCT (p<0.05). The Bulldog and French Bulldog breeds had a greater predisposition to HG-MCT (p<0.05) and the Pitbull, Mixed-breed and Pug, were the most frequently associated with the development of MCT, without predisposition to a specific histological grade. The most common location was the trunk, with 20.4% of cases of HG-MCT and 18.6% of LG-MCT, with no significant differences (p>0.05). Conclusions: the findings highlight the relevance of age and breed in the diagnosis and management of MCT. Dogs of certain breeds and ages may be more likely to be susceptible to more aggressive forms of the tumor, which is relevant for clinical management and early risk identification.